Democratic society and human needs - Noonan, Jeff (McGill-Queen's studies in the history of ideas, 2006)
In Democratic Society and Human Needs Noonan examines the moral grounds for liberalism and democracy, arguing that contemporary democracy was created through needs-based struggles against classical liberal rights, which are essentially exclusionary. For him, a democratic society is one in which human beings collectively control necessary life-resources, using them to promote the essential human value of free capability realization. His critique of globalization and liberal-capitalism vindicates radical social and economic democratization and provides an essential step towards understanding the vast discrepancies between rich and poor within and between democratic countries.